Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/aur.2711
|View full text |Cite
|
Sign up to set email alerts
|

A further study of relations between motor impairment and social communication, cognitive, language, functional impairments, and repetitive behavior severity in children with ASD using the SPARK study dataset

Abstract: Motor impairments are pervasive and persistent in children with autism spectrum disorder (ASD) throughout childhood and adolescence. Based on recent studies examining motor impairments in children with ASD between 5 and 15 years (i.e., SPARK study sample), 87–88% of this population is at‐risk for a motor impairment, these problems persisted until 15 years, and related to their core (social communication skills and repetitive behaviors [RBs]) and comorbid (language, cognitive, and functional) impairments. Persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
59
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 116 publications
4
59
0
1
Order By: Relevance
“…Dr. Bhat concluded that these findings highlight, "the need to recognize motor impairments as one of the diagnostic criteria or specifiers for ASD, and the need for appropriate motor screening and assessment of children with ASD" (Bhat, 2021, p. 202). She recently reiterated this claim in a follow-up publication using the same sample (Bhat et al, 2022). While we agree with the recommendation regarding screening and assessment of motor problems in children with ASD (as well as all children), we do not agree that there is enough evidence to support inclusion of motor impairments within the ASD definition.…”
mentioning
confidence: 58%
“…Dr. Bhat concluded that these findings highlight, "the need to recognize motor impairments as one of the diagnostic criteria or specifiers for ASD, and the need for appropriate motor screening and assessment of children with ASD" (Bhat, 2021, p. 202). She recently reiterated this claim in a follow-up publication using the same sample (Bhat et al, 2022). While we agree with the recommendation regarding screening and assessment of motor problems in children with ASD (as well as all children), we do not agree that there is enough evidence to support inclusion of motor impairments within the ASD definition.…”
mentioning
confidence: 58%
“…In response to Bhat's call for inclusion of motor deficits in ASD diagnostic criteria (Bhat, 2021;Bhat et al, 2022), Bishop et al (2022) take the conservative stance that no such extension can be justified in the absence of compelling evidence for motor deficits as a "core" feature. Bishop et al argue that Bhat's analysis of the SPARK data set fails to meet this bar because it does not prove that motor deficits might not be more parsimoniously explained by comorbid intellectual disability, 1 and because it depends on the Developmental Coordination Disorder Questionnaire (DCDQ), a parent-report screener which can confound motor skills with social participation in motor activities.…”
mentioning
confidence: 99%
“…We are writing to continue the dialog from Bishop et al (2022) and Bhat (2022) about the inclusion of the motor domain in future autism spectrum disorder (ASD) definitions. At the center of this dialog are a series of papers based on the Simons Powering Autism Research (SPARK) database showing the pervasiveness of motor impairments in youth on the autism spectrum based on the Developmental Coordination Disorder-Questionnaire (DCD-Q; Bhat, 2020;Bhat, 2021;Bhat et al, 2022). Within the large SPARK sample (n's > 10,000), more than 85% of youth on the autism spectrum exhibited DCD-Q scores consistent with elevated risk of motor impairment (Bhat, 2020;Bhat, 2021;Bhat et al, 2022;Ketcheson et al, 2021).…”
mentioning
confidence: 99%
“…At the center of this dialog are a series of papers based on the Simons Powering Autism Research (SPARK) database showing the pervasiveness of motor impairments in youth on the autism spectrum based on the Developmental Coordination Disorder-Questionnaire (DCD-Q; Bhat, 2020;Bhat, 2021;Bhat et al, 2022). Within the large SPARK sample (n's > 10,000), more than 85% of youth on the autism spectrum exhibited DCD-Q scores consistent with elevated risk of motor impairment (Bhat, 2020;Bhat, 2021;Bhat et al, 2022;Ketcheson et al, 2021). We agree with Bhat that these results provide evidence that warrants the consideration of motor impairments as a diagnostic criterion for ASD.…”
mentioning
confidence: 99%
See 1 more Smart Citation